Encapsulation of fenofibrate in solid lipid microparticles by central composite face-centred guided by electrospray - Azhar, Muhammad Fitri; Mohd Rus, Shaiqah; Haris @ Harith, Muhammad Salahuddin; Yang, Mingshi; Mu, Huiling (2020)
Background: Electrospray is a method able to produce monodispersed particles using applied electric field to deform the interface of liquid coming out from a capillary. Objectives: The abstract aims to investigate the influence of electrospray critical process parameters (CPPs), including: flow rate, solid concentration and tip-to-collector distance on the critical quality attributes (CQAs) of electrosprayed fenofibrate microparticles such as: particle size and yield. Methods: Central composite face-centred (CCF) design was carried out and analysed using partial least square (PLS). Results: The results from the PLS analysis were used to develop models and identify an optimal operating space (OOS). The particle size and the yield models were significant with p-value (<0.05). Flow rate and solid concentration parameters significantly affected the particle size and yield, respectively. A lower flow rate will produce smaller particle size of electrospray particles. Particle size below 2 μm can be obtained when the flow rate is below 13 μL/min for solid concentration between 1-3% (w/w) at 10 cm tip-to-collector distance. In order to increase yield up to 80%, solid concentration should be around 2.8% electrosprayed at distance of 10.25 cm. Discussion and conclusions: Electrospray technique can be used to encapsulate solid lipid fenofibrate microparticles by controlling the parameters including flow rate and solid concentration. The knowledge gained using CCF approach in this study will help in rational experimental design to achieve desired electrospray solid lipid fenofibrate microparticles characteristics.